2018
DOI: 10.1089/fpd.2017.2339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Staphylococcus aureus Isolated from Food Products in Western Algeria

Abstract: The current study aimed to characterize Staphylococcus aureus isolates from foodstuffs collected from western Algeria. A total of 153 S. aureus isolates from various raw and processed foods were obtained and identified using matrix-assisted laser desorption and ionization time-of-flight mass spectrometry. Isolates were characterized by antimicrobial susceptibility testing and toxin gene detection. Methicillin-resistant Staphylococcus aureus (MRSA) isolates were identified by detection of the mecA gene and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 51 publications
21
34
2
Order By: Relevance
“…In our study, the S. aureus contamination rate was lower than previously observed by Chaalal et al (2018) in Algeria. These authors reported a prevalence of 30Á9% out of 495 analysed samples, including raw and processed foods.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In our study, the S. aureus contamination rate was lower than previously observed by Chaalal et al (2018) in Algeria. These authors reported a prevalence of 30Á9% out of 495 analysed samples, including raw and processed foods.…”
Section: Discussioncontrasting
confidence: 74%
“…In Algeria, the proportion of MRSA demonstrated a high increase in the community and healthcare settings; the European clone ST80-IV, producer of the Panton-Valentine Leukocidin (PVL), has being detected (Antri et al 2011;Djahmi et al 2013;Chaalal et al 2018). A previous study of our group (Titouche et al 2019) was focusing on analysing dairy products obtained in 2014-2015, in which MRSA was isolated from some raw milk and acidified milk samples.…”
Section: Introductionmentioning
confidence: 99%
“…In Algeria, pathogenicity and antimicrobial resistance of staphylococci were investigated in clinical and food samples [21][22][23]. However, the biofilm-forming ability of Staphylococcus isolates and their genetic determinants were rarely evaluated in Algeria [24].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the over than 80% similarity, 36 S. aureus isolates were classi ed in 9 different pro les with 43 to 100% similarities. Isolates No 2,11,20,24,35,5,12,13 and 36 were classi ed in diverse pro les. The lowest similarity (43%) was found for isolates No 20, 11, 2 and 24.…”
Section: Molecular Typing Of S Aureus Strainsmentioning
confidence: 99%
“…Some potential virulence factors are accompanied in the pathogenesis of clinical infections and in some cases foodborne diseases caused by S. aureus [8,11]. Toxic shock syndrome toxin-1 (tsst-1), coagulase encoding gene (coa), exfoliative toxins A and B (eta and etb) and clumping factor (clfA) are frequently detected in S. aureus strains isolated from human clinical infections and foodstuffs [8,11,12].…”
mentioning
confidence: 99%